Pengaruh Latihan Jump to Box terhadap Kemampuan Lay Up Shoot Siswa Ekstrakurikuler Basket SMK Negeri 2 Palembang - Bagus Setiawan; Hengki Kumbara; Puput Sekar Sari (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This research aims to determine the effect of jump to box training on the lay up shoot ability of basketball extracurricular students at SMK NEGERI 2 Palembang. This research uses an experimental method. This research is a quantitative research that uses the